Trend of Dengue Hemorrhagic Fever (DHF) in the Last 5 Years in North Sumatra Province, 2018-2022 - Zuhair, Raisa Daffa; Putri, Eka Syah; Susanti, Nofi; Zahra, Mauliza; Vaudi, Tazkia (Universitas Teuku Umar, 2024)
Dengue Hemorrhagic Fever is a disease caused by the dengue virus identified by the appearance of fever for 2 to 7 days. This disease belongs to the Arthropod-Borne Virus class, the genus Flavivirus, and belongs to the Flaviviridae family. Dengue infection is an infectious disease that has the potential to become an outbreak (extraordinary event). In addition, this disease can also be caused by the environment and people's behavior, which is transmitted through the bite of the Aedes aegpty and Aedes albopictus mosquitoes. This research uses descriptive method and this research uses secondary data. In 2018-2022 the highest peak of DHF cases occurred in 2020, this was due to high rainfall and high humidity making the development of mosquitoes even higher. Of the several districts/cities, the prevalence rate was higher in Deli Serdang and Medan districts. The CFR rate increased in 2019 compared to 2018.The description of dengue hemorrhagic fever in the last 5 years in North Sumatra Province in 2018-2022 is fluctuating. It can be seen that in 2020 the peak of DHF cases was found in North Sumatra with a prevalence rate of 7,769 cases. Meanwhile, based on the description of the CFR, many occurred in 2019 with a percentage of 18.202%, then in the following year there was a decrease of 0.256%.